Autonomous Navigation onto Autodocking Drone System using Computer Vision - KRISTIANA, LISA; MAULANA, KEINDRA BAGAS; FASYA, SHAFIRA KURNIA; DAFY, MUHAMMAD ZUFAR; JANUAR, MUKTIADI AKHMAD (Institut Teknologi Nasional, Bandung, 2025)
Autodocking is a sophisticated technology that allows drones to land automatically at a predetermined docking station. Computer vision plays an important role in the drone autodocking system, allowing the drone to